Soft hydrophilic contact lens material, soft hydrophilic contact lens as well as preparation method and application of soft hydrophilic contact lens
By using hydrophilic monomers and antioxidant monomers in soft contact lens materials, combining crosslinking agents and initiators to form a network structure, the problem of dry eye symptoms during wearing soft contact lenses is solved, and the freedom is reduced and inflammatory responses, improving wear comfort and biosafety.
Patent Information
- Application Number
- CN202411276332.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-06-21
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Existing soft contact lenses are likely to cause dry eye symptoms during wearing, and existing contact lenses lack other functional designs, which cannot effectively reduce the free radical concentration and inflammatory response in tears.
Materials combined with hydrophilic monomers and antioxidant monomers are used to form a network structure through crosslinking agents and initiators, and the antioxidant is distributed stably, improving the antioxidant properties and biosafety of the material, reducing free radical levels and inflammatory responses.
It effectively reduces the dry eye symptoms during contact lens wear, improves wearing comfort, and provides cell ultraviolet protection function, enhancing the biosafety of the material.
Smart Images

Figure BDA0005040293980000021 
Figure BDA0005040293980000031 
Figure BDA0005040293980000061
Abstract
Description
[0001] This application claims the priority of patent application number 2024108111010. The filing date of the prior application is June 21, 2024. The name of the invention is a soft hydrophilic contact lens material, soft hydrophilic contact lens, and preparation method and application thereof. Technical Field
[0002] The invention belongs to the technical field of water contact lenses, and relates to a soft hydrophilic contact lens material, a soft hydrophilic contact lens, and a preparation method and application thereof. Background Art
[0003] Ocular surface dry eye is a common ophthalmic disease with a complex pathogenesis involving tear film stability, ocular surface inflammatory response, and the balance of the ocular surface microenvironment. Wearing soft contact lenses can affect the stability of the ocular surface tear environment, causing discomfort and even complications. Surveys show that wearing soft contact lenses can increase the risk of dry eyes by 1.93 to 2.96 times, and clinical studies have also shown that about 30% to 50% of soft contact lens wearers have dry eye symptoms. Soft contact lenses may increase tear osmotic pressure by inducing tear evaporation and changes in electrolyte concentration. Hyperosmotic pressure can cause morphological changes such as cell dehydration, while activating a series of signal transduction pathways, producing oxidative free radicals, inducing inflammatory responses and cell apoptosis, causing and aggravating dry eyes. At present, dry eye treatment uses eye drops or eye drops, but patient compliance is not high, and the bioavailability is not high (that is, most of it will be metabolized by tears), and if excessive drops are added, there will be biological toxicity. Therefore, it is very important to reduce the level of oxidative free radicals and tear inflammatory factors from the source to reduce dry eye symptoms during wearing.
[0004] However, currently, domestic contact lenses have no other functional designs except for ophthalmic applications such as myopia correction. Therefore, in this field, it is hoped to develop a water contact lens that can effectively reduce the concentration of free radicals in tears, reduce inflammatory responses, and thus improve the dry eye sensation during wearing. Summary of the invention
[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a soft hydrophilic contact lens material, a soft hydrophilic contact lens and a preparation method and application thereof.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In one aspect, the present invention provides a soft hydrophilic contact lens material, wherein the soft hydrophilic contact lens material comprises the following components in percentage by weight:
[0008] The hydrophilic monomer comprises 70% to 99%, the antioxidant monomer comprises 0.1% to 10%, the cross-linking agent comprises 0.05% to 6%, the initiator comprises 0.005% to 5%, and the diluent comprises 0.5% to 15%.
[0009] The hydrophilic monomer and the antioxidant monomer are used in the present invention, so that when preparing the soft hydrophilic contact lens, the monomers can be copolymerized under the action of the crosslinking agent and the initiator to form a network structure, so that the antioxidant monomer is stably distributed in the network structure formed by the copolymerization, wherein the hydrophilic monomer ensures that the material has high softness and improves the wearing comfort, and the antioxidant monomer improves the antioxidant performance of the soft hydrophilic contact lens material, reduces the free radicals in the contact lens wearing process, thereby reducing the possibility of inflammatory reaction and the possibility of dry eye of the contact lens, and the antioxidant monomer has the function of ultraviolet absorption, which can bring the effect of cell ultraviolet protection, and because both the hydrophilic monomer and the antioxidant monomer have good biological safety, the safety of the material is improved.
[0010] Preferably, the hydrophilic monomer is selected from at least one of hydroxyethyl methacrylate (HEMA), methacrylic acid (MAA), N-vinyl pyrrolidone (NVP), N,N-dimethylacrylamide, acrylic acid, hydroxyethyl acrylate, hydroxybutyl methacrylate, hydroxybutyl acrylate, N-vinyl acetamide (NVA) or N-vinyl-N-methylacetamide.
[0011] Preferably, the hydrophilic monomer is a combination of hydroxyethyl methacrylate and methacrylic acid.
[0012] Preferably, the weight ratio of hydroxyethyl methacrylate to methacrylic acid in the combination of hydroxyethyl methacrylate and methacrylic acid is 50:1 to 80:1, for example 50:1, 53:1, 55:1, 58:1, 60:1, 63:1, 66:1, 68:1, 70:1, 73:1, 75:1, 78:1 or 80:1.
[0013] In the soft hydrophilic contact lens material of the present invention, the weight percentage content of the hydrophilic monomer is 70% to 99%, for example, it can be 70%, 73%, 75%, 78%, 80%, 83%, 85%, 88%, 90%, 93%, 95%, 98% or 99%. In the present invention, if the weight percentage content of the hydrophilic monomer is lower than 70%, the water content of the soft hydrophilic contact lens material will be too low, and the comfort of wearing the contact lens will be reduced. If the weight percentage content of the hydrophilic monomer is higher than 99%, the content of auxiliary agents such as crosslinking agents and initiators will be too low, and the formability of the contact lens will be reduced.
[0014] Preferably, the antioxidant monomer is an antioxidant monomer containing a carbon-carbon unsaturated bond.
[0015] Preferably, the antioxidant monomer is at least one of a Biginelli-type monomer or a Hantzsch-type monomer.
[0016] Preferably, the antioxidant monomer is a combination of at least one of the following compounds:
[0017]
[0018]
[0019] In the soft hydrophilic contact lens material of the present invention, the weight percentage content of the antioxidant monomer is 0.1% to 10%, for example, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 1.8%, 2%, 2.5%, 2.8%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%. In the present invention, if the content of the antioxidant monomer is lower than 0.1%, the free radical scavenging effect of the soft hydrophilic contact lens material is low, and the effect of improving dry eyes is not obvious. If the content of the antioxidant monomer is higher than 10%, the moisture retention of the soft hydrophilic contact lens material is low, the water evaporation rate is too fast, and a certain eye irritation is generated after wearing.
[0020] Preferably, the crosslinking agent is selected from ethylene glycol dimethacrylate (EGDMA) and / or allyl methacrylate.
[0021] In the soft hydrophilic contact lens material of the present invention, the weight percentage content of the crosslinking agent is 0.05% to 6%, for example, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%.
[0022] Preferably, the initiator is at least one selected from Irgacure 819, azobisisoheptanenitrile, benzoin methyl ether, 2-hydroxy-2-methyl-1-phenylpropanone, and 2,2-diethoxyacetophenone.
[0023] In the soft hydrophilic contact lens material of the present invention, the weight percentage content of the initiator is 0.005% to 5%, for example, 0.005%, 0.008%, 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.5%, 2.8%, 3%, 3.5%, 3.8%, 4%, 4.3%, 4.5%, 4.8% or 5%.
[0024] Preferably, the diluent is selected from glycerol.
[0025] In the soft hydrophilic contact lens material of the present invention, the weight percentage content of the diluent is 0.5% to 15%, for example, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.
[0026] Preferably, the soft hydrophilic contact lens material further comprises a colorant.
[0027] Preferably, the colorant is selected from at least one of pigment violet, phthalocyanine green, titanium dioxide, cobalt chrome blue, chromium trioxide, red iron oxide, phthalocyanine blue, reactive blue, reactive yellow, reactive green, and vitamin B12.
[0028] Preferably, the weight percentage content of the colorant in the soft hydrophilic contact lens material is 0.1% to 1%, for example 0.1%, 0.3%, 0.5%, 0.8% or 1%.
[0029] In the present invention, the method for preparing the soft hydrophilic contact lens material comprises the following steps:
[0030] The hydrophilic monomer, the antioxidant monomer, the cross-linking agent, the initiator, the diluent and the optional colorant are mixed uniformly to obtain the soft hydrophilic contact lens material.
[0031] Preferably, the mixing is performed under stirring at room temperature.
[0032] In another aspect, the present invention provides a soft hydrophilic contact lens, which is prepared from the soft hydrophilic contact lens material as described above.
[0033] In another aspect, the present invention provides a method for preparing the soft hydrophilic contact lens as described above, the method comprising the following steps:
[0034] (1) injecting a soft hydrophilic contact lens material into a female mold of a mold, then pressing the male mold into the female mold for mold closing, placing the mold after mold closing into a curing machine, and polymerizing the monomer under ultraviolet irradiation;
[0035] (2) After the polymerization is completed, the male and female molds are separated, and the lens is kept in the female mold. The soft hydrophilic contact lens dry sheet is taken out and hydrated and extracted, and surface inspection is performed during the process;
[0036] (3) After the hydration extraction is completed and the soft hydrophilic contact lens that has passed the surface inspection is sterilized to obtain the soft hydrophilic contact lens.
[0037] Preferably, the mold in step (1) is a plastic male mold and a plastic female mold for molding soft hydrophilic contact lenses, which are injected by an injection molding machine according to the design and are qualified by R value detection.
[0038] In the present invention, the R value refers to the radius of curvature of the mold surface.
[0039] Preferably, the master mold in step (1) is a master mold that is surface treated with plasma to ensure the wettability of its surface and to ensure that the subsequent lenses can retain the master mold. The basis for judging whether the master mold is qualified is to test the degree of surface treatment of the master mold with a dyne pen, and it is judged to be qualified if the wettability exceeds 5 seconds.
[0040] In the present invention, the plasma treated master mold is placed on a lens making plate, the base material liquid of the soft hydrophilic contact lens is injected into the master mold by a liquid injection machine, and then the male mold is pressed into the female mold for mold closing.
[0041] Preferably, the ultraviolet irradiation in step (1) is performed using an ultraviolet lamp.
[0042] Preferably, the wavelength of the ultraviolet irradiation is controlled at 405-410 nm.
[0043] Preferably, the energy value of the ultraviolet irradiation is controlled at 10-150 mw / cm 2 , for example 10mw / cm 2 、11mw / cm 2 、12mw / cm 2 、13mw / cm 2 、14mw / cm 2 or 15mw / cm 2 .
[0044] Preferably, the polymerization time of step (1) is controlled within 10 to 60 min, for example, 10 min, 15 min, 18 min, 20 min, 23 min, 25 min, 28 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min.
[0045] Preferably, the hydration extraction temperature in step (2) is controlled at 25-80°C, for example, 25°C, 28°C, 30°C, 35°C, 38°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, and the hydration extraction time is controlled at 60-180min, for example, 60min, 65min, 70min, 75min, 80min, 90min, 100min, 120min, 140min, 150min, 160min, 170min or 180min.
[0046] Preferably, the sterilization in step (3) is to place the soft hydrophilic contact lens that has completed hydration extraction and passed the surface inspection into a PP cup container, inject a preservation solution, and seal it with a cover; then perform a high-temperature wet heat sterilization treatment.
[0047] Preferably, the sterilization temperature is 100-130°C, for example, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C, and the sterilization time is 10-45min, for example, 10min, 13min, 15min, 20min, 25min, 28min, 30min, 35min, 38min, 40min, 43min or 45min.
[0048] In another aspect, the present invention provides a drug sustained-release material, which comprises the soft hydrophilic contact lens material as described above.
[0049] In another aspect, the present invention provides a bandage lens, wherein the raw materials for preparing the bandage lens include the soft hydrophilic contact lens material as described above.
[0050] In another aspect, the present invention provides a wound dressing, comprising the soft hydrophilic contact lens material as described above.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] The invention utilizes hydrophilic monomers, antioxidant monomers, crosslinking agents, initiators and diluents to prepare soft hydrophilic contact lens materials, and the soft hydrophilic contact lenses are prepared from the materials. Under the action of the crosslinking agent and the initiator, the monomers are copolymerized to form a network structure, so that the antioxidant monomers are stably distributed in the network structure formed by the copolymerization, so that the soft hydrophilic contact lens material has good antioxidant performance, reduces free radicals in the process of wearing contact lenses, thereby reducing the possibility of inflammatory reactions and the possibility of dry eyes caused by contact lenses. At the same time, the antioxidant monomers have the function of absorbing ultraviolet rays, can bring about the effect of ultraviolet protection of cells, and have good biological safety.
[0053] The soft hydrophilic contact lens material of the present invention can be applied to contact lenses, drug sustained-release materials, bandage lenses, wound dressings, etc., and has broad application prospects. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0055] Example 1
[0056] In this embodiment, a soft hydrophilic contact lens material is provided, and the soft hydrophilic contact lens material comprises the following components in weight percentage:
[0057] Hydrophilic monomer 86.5%, antioxidant monomer 0.5%, cross-linking agent 2%, initiator 1%, diluent 10%.
[0058] The hydrophilic monomers are HEMA and MAA, and the weight ratio of the two is 66:1. The antioxidant monomer is M1: The crosslinker was EGDMA, the initiator was Irgacure 819, and the diluent was glycerol.
[0059] The hydrophilic monomer, the antioxidant monomer, the cross-linking agent, the initiator and the diluent are mixed uniformly under stirring at room temperature to obtain the soft hydrophilic contact lens material.
[0060] Example 2
[0061] The only difference from Example 1 is that the soft hydrophilic contact lens material comprises the following components in percentage by weight:
[0062] Hydrophilic monomer 86%, antioxidant monomer 1%, cross-linking agent 2%, initiator 1%, diluent 10%.
[0063] Example 3
[0064] The only difference from Example 1 is that the soft hydrophilic contact lens material comprises the following components in percentage by weight:
[0065] Hydrophilic monomer 85.5%, antioxidant monomer 1.5%, cross-linking agent 2%, initiator 1%, diluent 10%.
[0066] Example 4
[0067] The only difference from Example 1 is that the soft hydrophilic contact lens material comprises the following components in percentage by weight:
[0068] Hydrophilic monomer 85%, antioxidant monomer 2%, cross-linking agent 2%, initiator 1%, diluent 10%.
[0069] Example 5
[0070] The only difference from Example 1 is that the soft hydrophilic contact lens material comprises the following components in percentage by weight:
[0071] Hydrophilic monomer 84.5%, antioxidant monomer 2.5%, cross-linking agent 2%, initiator 1%, diluent 10%.
[0072] Example 6
[0073] The only difference from Example 1 is that the soft hydrophilic contact lens material comprises the following components in percentage by weight:
[0074] Hydrophilic monomer 84%, antioxidant monomer 3%, cross-linking agent 2%, initiator 1%, diluent 10%.
[0075] Example 7
[0076] The only difference from Example 1 is that the soft hydrophilic contact lens material comprises the following components in percentage by weight:
[0077] Hydrophilic monomer 81%, antioxidant monomer 6%, cross-linking agent 6%, initiator 2%, diluent 5%.
[0078] Example 8
[0079] The only difference from Example 1 is that the soft hydrophilic contact lens material comprises the following components in percentage by weight:
[0080] Hydrophilic monomer 73.5%, antioxidant monomer 10%, cross-linking agent 1%, initiator 0.5%, diluent 15%.
[0081] Example 9
[0082] The only difference from Example 1 is that the antioxidant monomer M1 in Example 1 is replaced by the following antioxidant monomer M2:
[0083]
[0084] Example 10
[0085] The only difference from Example 2 is that the antioxidant monomer M1 in Example 2 is replaced by the following antioxidant monomer M2:
[0086]
[0087] Embodiment 11
[0088] The only difference from Example 3 is that the antioxidant monomer M1 in Example 3 is replaced by the following antioxidant monomer M2:
[0089]
[0090] Example 12
[0091] The only difference from Example 4 is that the antioxidant monomer M1 in Example 4 is replaced by the following antioxidant monomer M2:
[0092]
[0093] Embodiment 13
[0094] The only difference from Example 5 is that the antioxidant monomer M1 in Example 5 is replaced by the following antioxidant monomer M2:
[0095]
[0096] Embodiment 14
[0097] The only difference from Example 6 is that the antioxidant monomer M1 in Example 6 is replaced by the following antioxidant monomer M2:
[0098]
[0099] Embodiment 15
[0100] The only difference from Example 14 is that the soft hydrophilic contact lens material includes the following components in weight percentage: 83.5% hydrophilic monomer, 3.5% antioxidant monomer, 2% crosslinking agent, 1% initiator, and 10% diluent.
[0101] Example 16
[0102] The only difference from Example 14 is that the soft hydrophilic contact lens material comprises the following components in percentage by weight: 83% hydrophilic monomer, 4% antioxidant monomer, 2% cross-linking agent, 1% initiator, and 10% diluent.
[0103] Embodiment 17
[0104] The only difference from Example 7 is that the antioxidant monomer M1 in Example 7 is replaced by the following antioxidant monomer M2:
[0105]
[0106] Embodiment 18
[0107] The only difference from Example 8 is that the antioxidant monomer M1 in Example 8 is replaced by the following antioxidant monomer M2:
[0108]
[0109] Embodiment 19
[0110] The only difference from Example 1 is that the antioxidant monomer M1 in Example 1 is replaced by the following antioxidant monomer M3:
[0111]
[0112] Embodiment 20
[0113] The only difference from Example 2 is that the antioxidant monomer M1 in Example 2 is replaced by the following antioxidant monomer M3:
[0114]
[0115] Embodiment 21
[0116] The only difference from Example 3 is that the antioxidant monomer M1 in Example 3 is replaced by the following antioxidant monomer M3:
[0117]
[0118] Embodiment 22
[0119] The only difference from Example 3 is that the antioxidant monomer M1 in Example 3 is replaced by the following antioxidant monomer M4:
[0120]
[0121] Embodiment 23
[0122] The only difference from Example 6 is that the antioxidant monomer M1 in Example 6 is replaced by the following antioxidant monomer M4:
[0123]
[0124] Embodiment 24
[0125] The only difference from Example 1 is that the antioxidant monomer M1 in Example 1 is replaced by the following antioxidant monomer M5: (Prepared with reference to paragraphs 0062-0064 of the specification of CN109942760A).
[0126] Embodiment 25
[0127] The only difference from Example 4 is that the antioxidant monomer M1 in Example 4 is replaced by the following antioxidant monomer M5:
[0128]
[0129] Embodiment 26
[0130] The only difference from Example 7 is that the antioxidant monomer M1 in Example 7 is replaced by the following antioxidant monomer M5:
[0131]
[0132] Embodiment 27
[0133] The only difference from Example 1 is that the antioxidant monomer M1 in Example 1 is replaced by the following antioxidant monomer M6: (Its preparation is carried out according to step (1) in Example 1 in CN111004359A).
[0134] Embodiment 28
[0135] The only difference from Example 4 is that the antioxidant monomer M1 in Example 4 is replaced by the following antioxidant monomer M6:
[0136]
[0137] Embodiment 29
[0138] The only difference from Example 7 is that the antioxidant monomer M1 in Example 7 is replaced by the following antioxidant monomer M6:
[0139]
[0140] Embodiment 30
[0141] The only difference from Example 1 is that the antioxidant monomer M1 in Example 1 is replaced by the following antioxidant monomer M7: (Its preparation is carried out according to step (1) in Example 1 of CN111004359A, wherein 4-hydroxybenzaldehyde is replaced by 4-hydroxy-3-methoxybenzaldehyde).
[0142] Embodiment 31
[0143] The only difference from Example 4 is that the antioxidant monomer M1 in Example 4 is replaced by the following antioxidant monomer M7:
[0144]
[0145] Embodiment 32
[0146] The only difference from Example 7 is that the antioxidant monomer M1 in Example 7 is replaced by the following antioxidant monomer M7:
[0147]
[0148] Embodiment 33
[0149] The only difference from Example 1 is that the antioxidant monomer M1 in Example 1 is replaced by the following antioxidant monomer M8:
[0150]
[0151] Embodiment 34
[0152] The only difference from Example 4 is that the antioxidant monomer M1 in Example 4 is replaced by the following antioxidant monomer M8:
[0153]
[0154] Embodiment 35
[0155] The only difference from Example 7 is that the antioxidant monomer M1 in Example 7 is replaced by the following antioxidant monomer M8:
[0156]
[0157] Embodiment 36
[0158] The only difference from Example 1 is that the antioxidant monomer M1 in Example 1 is replaced by the following antioxidant monomer M8: And the dosage of each component in the soft hydrophilic contact lens material is as follows:
[0159] Hydrophilic monomer 99%, antioxidant monomer 0.1%, cross-linking agent 0.35%, initiator 0.05%, diluent 0.5%.
[0160] Embodiment 37
[0161] The only difference from Example 1 is that the weight ratio of HEMA to MAA is 50:1.
[0162] Embodiment 38
[0163] The only difference from Example 1 is that the weight ratio of HEMA to MAA is 80:1.
[0164] Embodiment 39
[0165] The only difference from Example 1 is that the hydrophilic monomer is only HEMA, and its content is 86.5%.
[0166] Embodiment 40
[0167] The only difference from Example 1 is that the hydrophilic monomer is only MAA, and its content is 86.5%.
[0168] Embodiment 41
[0169] The only difference from Example 5 is that the antioxidant monomer is a combination of M1 and M3, and the amounts of the two are 1.5% and 1% respectively.
[0170] Embodiment 42
[0171] The only difference from Example 6 is that the antioxidant monomer is a combination of M1 and M4, and the amounts of the two are 1% and 2% respectively.
[0172] Embodiment 43
[0173] The only difference from Example 2 is that the antioxidant monomer is a combination of M1 and M2, and the amounts of the two are 0.5% and 0.5% respectively.
[0174] Embodiment 44
[0175] The only difference from Example 4 is that the antioxidant monomer is a combination of M5 and M6, and the amounts of the two are 1% and 1% respectively.
[0176] Embodiment 45
[0177] The only difference from Example 4 is that the antioxidant monomer is a combination of M6 and M8, and the amounts of the two are 1% and 1% respectively.
[0178] Comparative Example 1
[0179] The only difference from Example 1 is that the antioxidant monomer used is curcumin (CAS: 458-37-7)
[0180] Comparative Example 2
[0181] The only difference from Example 1 is that the antioxidant monomer used is silymarin, and the structure is as follows:
[0182]
[0183] Comparative Example 3
[0184] The only difference from Example 1 is that poly(ethylene glycol) methacrylate is used to replace the antioxidant monomer in Example 1.
[0185] Comparative Example 4
[0186] The only difference from Example 1 is that the soft hydrophilic contact lens material comprises the following components in percentage by weight:
[0187] Hydrophilic monomer 87%, cross-linking agent 2%, initiator 1%, diluent 10%.
[0188] Comparative Example 5
[0189] The only difference from Example 8 is that the soft hydrophilic contact lens material includes the following components in weight percentage:
[0190] Hydrophilic monomer 70.5%, antioxidant monomer 13%, cross-linking agent 1%, initiator 0.5%, diluent 15%.
[0191] Comparative Example 6
[0192] The only difference from Example 1 is that the soft hydrophilic contact lens material comprises the following components in percentage by weight:
[0193] Hydrophilic monomer 86.95%, antioxidant monomer 0.05%, cross-linking agent 2%, initiator 1%, diluent 10%.
[0194] Comparative Example 7
[0195] The only difference from Example 8 is that the soft hydrophilic contact lens material includes the following components in weight percentage:
[0196] Hydrophilic monomer 68%, antioxidant monomer 10%, cross-linking agent 6%, initiator 1%, diluent 15%.
[0197] Comparative Example 8
[0198] The only difference from Example 1 is that the soft hydrophilic contact lens material comprises the following components in percentage by weight:
[0199] Hydrophilic monomer 99.3%, antioxidant monomer 0.1%, cross-linking agent 0.05%, initiator 0.05%, diluent 0.5%.
[0200] Application Example 1
[0201] The soft hydrophilic contact lens material of Example 1 is used to prepare a soft hydrophilic contact lens, and the preparation method thereof comprises the following steps:
[0202] 1) Prepare the mold: Use an injection molding machine to inject the plastic male mold and plastic female mold for molding the soft hydrophilic contact lens according to the design, and perform R value test and prepare them for use after they are qualified;
[0203] 2) Master mold processing: The injected master mold is surface treated with Plasma. The qualified treatment is judged based on the degree of surface treatment of the master mold tested by a dyne pen. If the wetness exceeds 5 seconds, it is judged to be qualified to ensure the wetness of the surface and ensure that the subsequent lenses can retain the master mold;
[0204] 3) Injection and mold closing: placing the processed mother mold on the lens making plate, injecting the soft hydrophilic contact lens material liquid prepared in Example 1 into the mother mold by a liquid injection machine, and then pressing the male mold into the mother mold for mold closing;
[0205] 4) Polymerization and curing: Put the male and female molds after injection molding into a curing machine, and polymerize the monomers under the action of UV lamp to obtain a cured soft hydrophilic contact lens dry sheet; the irradiation wavelength of the UV lamp is controlled at 410nm, and the energy value of the UV lamp is controlled at 100mw / cm 2 , the polymerization time is 40min;
[0206] 6) Hydration extraction: After the polymerization and curing are completed, the male and female molds are separated, and the lens is kept in the female mold. The soft hydrophilic contact lens dry piece is taken out by a mold separating machine and placed in a hydration extraction disk for hydration extraction, during which a surface inspection is performed; the temperature of the hydration extraction is controlled at 50°C, and the time of the hydration extraction is controlled at 120 minutes; the specific operation of the surface inspection is: the soft hydrophilic contact lens dry piece is magnified 7 to 10 times in the hydration extraction buffer and observed with the naked eye, and the standards are: the lens has no inclusions that affect normal use, such as spots, residual debris, or crystal dendrite bubbles, etc.; there are no defects, such as surface cracks, broken edges, etc.; and the shape around the edge of the lens is uniform.
[0207] 7) Sterilization: Place the soft hydrophilic contact lenses after surface inspection in a PP cup container, inject preservation solution, cover with aluminum foil, and seal by hot pressing to achieve complete sealing; then place in a sterilization box and put into a sterilizer for high-temperature wet heat sterilization. The sterilization parameters are: temperature 120℃, time 30min.
[0208] Application Example 2-45 and Comparative Application Example 1-8
[0209] The only difference from Application Example 1 is that the soft hydrophilic contact lens material prepared in Example 1 is replaced by the soft hydrophilic contact lens material prepared in Examples 2-45 or Comparative Application Examples 1-8 respectively.
[0210] The diameter, base curve, center thickness, visible light transmittance and ultraviolet transmittance, water content and free radical scavenging rate of the soft hydrophilic contact lens prepared according to the corresponding example are tested. The test method is as follows:
[0211] (1) The diameter, base curve and center thickness are tested according to the mechanical properties test method of GB / T11417.6-2012.
[0212] (2) Visible light transmittance and ultraviolet transmittance are tested according to the light transmittance test method in GB / T11417.5-2012.
[0213] (3) The moisture content is tested according to the test method in GB / T11417.7-2012.
[0214] (4) Free radical scavenging efficiency: I. Prepare ABTS working solution: Take 76.8 mg of ABTS (2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid) and add water to make up to 20 mL; Take 13.2 mg of potassium persulfate and add water to make up to 20 mL. Mix the two evenly and let stand for more than 14 hours to make ABTS working solution with a shelf life of 2 weeks; II. Take 1.5 mL of ABTS working solution and add 40 mL (31.57 g) of ethanol to prepare ABTS detection solution, which should be prepared and used on the same day; III. Add 1 mL of ABTS to each well of a 12-well plate. Add ABTS test solution to the lens at the same time; let it stand for 1 hour; add 3mL of ethanol to dilute, take 3mL of the dilution to measure the transmittance at 734nm, measurement mode: select 680-740nm band, soft lens, take the reading at 734nm for recording, the absorbance of pure ABTS test solution is used as the control, each group of sample addition & measurement is 3 minutes apart, parallel test characterization is performed, free radical scavenging rate = (1-(1-transmittance of experimental group) / (1-transmittance of control group))×100%.
[0215] (5) Moisture retention test: the test method is as follows: the edge area of the contact lens is immersed in standard physiological saline, and the central area is exposed to air. Then, after removing the solution on the surface of the contact lens according to the test method in GB / T11417.7-2012, the water content at the 4-hour time point and the 8-hour time point is measured (the better the moisture retention, the higher the water content after a certain period of time after exposure to air).
[0216] The test results are shown in Tables 1-5 (the sample numbers in the tables represent samples tested in parallel, and the multiple values under one item in one embodiment in the tables represent the values obtained from the parallel sample tests).
[0217] Table 1
[0218]
[0219]
[0220]
[0221]
[0222]
[0223] Table 2
[0224]
[0225]
[0226]
[0227]
[0228] Table 3
[0229]
[0230]
[0231] Table 4
[0232]
[0233]
[0234] Table 5
[0235]
[0236]
[0237]
[0238]
[0239] Tests have shown that the soft hydrophilic contact lens of the present invention has good antioxidant properties, ultraviolet absorption properties, and moisturizing properties, and has good biological safety. It is easy to prepare soft hydrophilic contact lenses that meet national standards through traditional preparation processes such as photocuring.
[0240] In comparative application example 1, the solubility of curcumin in the raw material is relatively low, resulting in a low free radical elimination ability of the contact lens and an insignificant effect in improving dry eyes.
[0241] In comparative application example 2, the solubility of silymarin in the raw material is relatively low, resulting in a low free radical elimination ability of the contact lens and an insignificant effect in improving dry eyes.
[0242] In comparative application example 3, poly(ethylene glycol) methacrylate itself does not have antioxidant capacity, resulting in the contact lens having almost no free radical elimination capacity and basically no effect in improving dry eyes.
[0243] In comparative application example 4, no antioxidant monomer is added, resulting in the contact lens having almost no free radical elimination ability and basically no effect in improving dry eyes.
[0244] In comparative application example 5, the proportion of the antioxidant monomer is higher than 10%, the moisture retention of the contact lens is low, and the water evaporation rate is too fast, resulting in a certain eye irritation after wearing.
[0245] In comparative application example 6, the proportion of the antioxidant monomer is lower than 0.1%, the free radical elimination ability of the contact lens is reduced, and the effect of improving dry eyes is not obvious.
[0246] In comparative application example 7, the proportion of the hydrophilic monomer is lower than 70%, and the water content of the contact lens is too low, and the comfort of the contact lens is reduced.
[0247] In comparative application example 8, the proportion of the hydrophilic monomer is higher than 99%, which results in too low content of auxiliary agents such as crosslinking agent and initiator, poor contact lens moldability, inability to produce molded contact lens products, and inability to obtain parameters.
[0248] The applicant declares that the present invention uses the above embodiments to illustrate the soft hydrophilic contact lens material, the soft hydrophilic contact lens and the preparation method and application thereof, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A soft hydrophilic contact lens material, characterized in that: The soft hydrophilic contact lens material comprises the following components in weight percentage: The hydrophilic monomer comprises 70% to 99%, the antioxidant monomer comprises 0.1% to 10%, the cross-linking agent comprises 0.05% to 6%, the initiator comprises 0.005% to 5%, and the diluent comprises 0.5% to 15%.
2. The soft hydrophilic contact lens material according to claim 1, characterized in that: The hydrophilic monomer is selected from at least one of hydroxyethyl methacrylate, methacrylic acid, N-vinyl pyrrolidone, N,N-dimethylacrylamide, acrylic acid, hydroxyethyl acrylate, hydroxybutyl methacrylate, hydroxybutyl acrylate, N-vinyl acetamide or N-vinyl-N-methylacetamide; Preferably, the hydrophilic monomer is a combination of hydroxyethyl methacrylate and methacrylic acid; Preferably, the weight ratio of hydroxyethyl methacrylate to methacrylic acid in the combination of hydroxyethyl methacrylate and methacrylic acid is 50:1 to 80:
1.
3. The soft hydrophilic contact lens material according to claim 1 or 2, characterized in that: The antioxidant monomer is an antioxidant monomer containing a carbon-carbon unsaturated bond; Preferably, the antioxidant monomer is at least one of a Biginelli type monomer or a Hantzsch type monomer; Preferably, the antioxidant monomer is any one or a combination of at least two of the following compounds:
4. The soft hydrophilic contact lens material according to any one of claims 1 to 3, characterized in that: The cross-linking agent is selected from ethylene glycol dimethacrylate and / or allyl methacrylate; Preferably, the initiator is selected from at least one of Irgacure 819, azobisisoheptanenitrile, benzoin methyl ether, 2-hydroxy-2-methyl-1-phenylpropanone or 2,2-diethoxyacetophenone; Preferably, the diluent is selected from glycerol; Preferably, the soft hydrophilic contact lens material further comprises a colorant; Preferably, the colorant is selected from at least one of pigment violet, phthalocyanine green, titanium dioxide, cobalt chrome blue, chromium trioxide, red iron oxide, phthalocyanine blue, reactive blue, reactive yellow, reactive green or vitamin B12; Preferably, the weight percentage content of the colorant in the soft hydrophilic contact lens material is 0.1% to 1%.
5. The method for preparing a soft hydrophilic contact lens material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The hydrophilic monomer, the antioxidant monomer, the cross-linking agent, the initiator, the diluent and the optional colorant are uniformly mixed to obtain the soft hydrophilic contact lens material; Preferably, the mixing is performed under stirring at room temperature.
6. A soft hydrophilic contact lens, characterized in that: The soft hydrophilic contact lens is prepared from the soft hydrophilic contact lens material according to any one of claims 1 to 4.
7. The method for preparing a soft hydrophilic contact lens according to claim 6, characterized in that: The preparation method comprises the following steps: (1) injecting a soft hydrophilic contact lens material into a female mold of a mold, then pressing the male mold into the female mold for mold closing, placing the mold after mold closing into a curing machine, and polymerizing the monomer under ultraviolet irradiation; (2) After the polymerization is completed, the male and female molds are separated, and the lens is kept in the female mold. The soft hydrophilic contact lens dry sheet is taken out and hydrated and extracted, and surface inspection is performed during the process; (3) sterilizing the soft hydrophilic contact lens that has been hydrated and extracted and passed the surface inspection to obtain the soft hydrophilic contact lens; Preferably, the mold in step (1) is a plastic male mold and a plastic female mold for molding a soft hydrophilic contact lens, which are injected by an injection molding machine according to the design and are qualified by R value detection; Preferably, the master mold in step (1) is a master mold that is surface treated with Plasma, and the basis for judging whether the master mold is qualified is: the degree of surface treatment of the master mold is tested by a dyne pen, and it is judged to be qualified if the wetting degree exceeds 5 seconds; Preferably, the ultraviolet irradiation in step (1) is performed using an ultraviolet lamp; Preferably, the wavelength of the ultraviolet irradiation is controlled at 405-410 nm; Preferably, the energy value of the ultraviolet irradiation is controlled at 10-150 mw / cm 2 ; Preferably, the polymerization time in step (1) is controlled within 10 to 60 minutes; Preferably, the hydration extraction temperature in step (2) is controlled at 25 to 80° C., and the hydration extraction time is controlled at 60 to 180 min. Preferably, the sterilization in step (3) is to place the soft hydrophilic contact lens that has completed the hydration extraction and passed the surface inspection into a PP cup container, inject a preservation solution, and seal it with a cover; then perform a high temperature wet heat sterilization treatment; Preferably, the sterilization temperature is 100-130° C., and the sterilization time is 10-45 min.
8. A drug sustained-release material, characterized in that: The drug sustained-release material comprises the soft hydrophilic contact lens material according to any one of claims 1 to 4.
9. A bandage spectacle, characterized in that: The raw materials for preparing the bandage lens include the soft hydrophilic contact lens material according to any one of claims 1 to 4.
10. A wound dressing, characterized in that: The wound dressing comprises the soft hydrophilic contact lens material according to any one of claims 1-4.
Citation Information
Patent Citations
3,4-dihydrothioferrocene pyrimidine-2-ketone polymer, as well as preparation method and application thereof
CN109942760A
Self-repairing antioxidant hydrogel based on boric acid ester bond
CN110372828A
Anti-X-ray water-soluble polymer containing 1, 4-dihydropyridine structure and preparation method thereof
CN111004359A
Preparation method and application of 1, 4-dihydropyridyl chitosan
CN113563495A
Antibacterial and antioxidant hydrogel for corneal contact lens and preparation method thereof
CN114381083A
Cited By
Composition for improving local tissue microenvironment and preparation method and application thereof
CN122212957A
